2021
DOI: 10.3892/etm.2021.10378
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin triggers prostate cancer cell apoptosis by inducing oxidative and endoplasmic reticulum stress via suppressing Nrf2 signaling

Abstract: Salinomycin is a polyether antiprotozoal antibiotic that is widely used as an animal food additive. Some antifungal, antiparasitic, antiviral and anti-inflammatory activities have been reported for salinomycin. Recently, the anti-cancer effect of salinomycin has been demonstrated in breast cancer; however, the underlying mechanism remains unknown. The present study aimed to investigate the functional roles of salinomycin in the progression of prostate cancer cells using the DU145 and PC-3 cell lines. Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Geyikoglu et al ( 40 ) demonstrated that boric acid decreased the 8-OHdG expression level in ischemia reperfusion injury by acting as an antioxidant, anti-inflammatory and antiapoptotic agent. The results of TAC, TOS and LDH assays supported the results from the 8-OHdG staining assay ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 74%
“…Geyikoglu et al ( 40 ) demonstrated that boric acid decreased the 8-OHdG expression level in ischemia reperfusion injury by acting as an antioxidant, anti-inflammatory and antiapoptotic agent. The results of TAC, TOS and LDH assays supported the results from the 8-OHdG staining assay ( 41 , 42 ).…”
Section: Discussionsupporting
confidence: 74%
“…Downregulating NRF2 increases ROS, oxidation of nucleic acids and lipids, decreases the activity of antioxidant enzymes, and increases the unfolded protein response and endoplasmic reticulum stress in advanced stage PCa (J. Yu et al, 2021). A plantbased polyphenol fraction upregulated ROS levels by decreasing NRF2 and increasing monoamine oxidase A activity, both in androgen-dependent LNCaP and androgenindependent PC3 and DU145 cells but not in normal cells.…”
Section: Nrf2 Modulators In Pre-clinical Pca Researchmentioning
confidence: 99%
“…The antibiotic, salinomycin, increases apoptosis via ER and oxidative stress in advanced PCa by suppressing NRF2 activity and expression of its target genes: HO-1, NQO1 and GCLC (J. Yu et al, 2021). In TRAMPC mouse models it was observed that the (T. Y.…”
Section: Nrf2 Modulators In Pre-clinical Pca Researchmentioning
confidence: 99%
“…Salinomycin is a monocarboxylic ionophore antibiotic isolated from the bacterium Streptomyces albus (15). Also, there are convincing evidences regarding the antifungal, antiparasitic, antiviral and anti-inflammatory properties of this compound (15).…”
Section: Introductionmentioning
confidence: 99%
“…Salinomycin is a monocarboxylic ionophore antibiotic isolated from the bacterium Streptomyces albus (15). Also, there are convincing evidences regarding the antifungal, antiparasitic, antiviral and anti-inflammatory properties of this compound (15). Lately, the anticancer effect of salinomycin has been highlighted due to its potential in apoptosis induction and downregulating the growth of various types of chemotherapeutic-resistant cancer cells (16).…”
Section: Introductionmentioning
confidence: 99%